P246 URINARY SODIUM–GUIDED I.V. DIURETIC THERAPY IN ACUTE HEART FAILURE: APPLICATION OF THE YALE DIURETIC PROTOCOL IN A REAL–WORLD ITALIAN SETTING. (18th May 2022) - Pellegrino, M; Gasparini, G; Ghianda, D; Villaschi, A; Oliva, A; Loiacono, F; Pagliaro, B; Natali Testona, N; Atuncar, M; Pini, D
Abstract: Background: Loop diuretics are the cornerstone of acutely decompensated heart failure (ADHF) treatment, but evidences on doses and administration modalities are still lacking. Veena S. et al have recently validated the Natriuretic Response Prediction Equation and applied it with the Yale Diuretic Protocol (YDP) in a clinical implementation cohort demonstrating its safety. Objectives: Our purpose is to test the applicability and safety of YDP for titration of diuretic therapy in a real–world in–hospital setting, as compared to standard diuretic therapy. METHODS From 15th September 2021 patients hospitalized with ADHF, almost one sign of congestion and need of i.v. diuretics were enrolled. Patients with active bleeding, hematocrit < 21%, or on dialysis were excluded. Patients were treated with i.v. diuretic therapy guided by urinary sodium (YDP–group) or by weight changes and urinary output (control group) based on logistic in–hospital reasons. Results: Thirty patients were included. Median age was 76.4 [IQR 68.3; 82.7] years old; median EF and glomerular filtration rate were 40% [IQR 30; 55] and 57.2 ml/min/m2 [IQR 44.9; 79.9], respectively. Nineteen (63.3%) patients were on chronic loop diuretic treatment. Ten (33.3%) patients were treated according to YDP. Main results are shown in the Table attached. YDP patients were younger (p = 0.02) and received shorter treatment with i.v. diuretics (YDP 36 [IQR 27; 48] hours, controls 48 [IQRS 38; 88] hours; p = 0.03). No differences in terms of total diuresis, weight loss at the end of i.v. diuretic therapy and length of hospitalization were shown. YDP patients experienced significant lower increase in creatinine during i.v. diuretic therapy (p = 0.02). The incidence of adverse events was comparable between groups, with equal hypotension rate (10%), and similar plasma levels of electrolytes at the end of i.v. diuretic therapy; YDP patients required less potassium supplementation. Reasons for i.v. diuretic therapy suspension were comparable between groups; 7 (70%) YDP patients concluded i.v. diuretic therapy for satisfactory decongestion, while only one patient because of hypotension and none because of worsening of renal function. Conclusion: In our reality the YDP appeared to be applicable, safe and comparable to the standard i.v. diuretic therapy in terms of in–hospital outcomes. These preliminary results need to be confirmed in a larger cohort and longer term outcomes still need to be explored.